Do Wind Turbines Have Adverse Health Impacts? - Christian Krekel; Johannes Rode; Alexander Roth (Institute of Labor Economics (IZA), 2023)
While wind power is considered key in the transition towards net zero, there are concerns about adverse health impacts on nearby residents. Based on precise geographical coordinates, we link a representative longitudinal household panel to all wind turbines in Germany and exploit their staggered rollout over two decades for identification. We do not find evidence of negative effects on general, mental, or physical health in the 12-Item Short Form Survey (SF- 12), nor on self-assessed health or doctor visits. We also do not find evidence for effects on suicides, an extreme measure of negative mental health outcomes, at the county level.
Keywords: D62; I10; Q20; Q42; R10; 330; wind turbines; externalities; health; renewable energy; difference-in-differences; event study